Diagnostic accuracy evaluation of individual or combinational fecal immunochemical test, M3 gene, KRAS mutation and tumor methylation burden in colorectal carcinoma - Xu, Junyue; Chen, Shuai; Niu, Hongxia; Zhao, Yahong; Wu, Xiaohong; Li, Yi; Zhang, Shana (Frontiers in Immunology, 2025)
ObjectiveThis study is aimed to develop multivariate prediction method in colorectal cancer (CRC) diagnosis.MethodologyM3 gene expression was determined using Fecal DNA extraction kits and performed by qRT-PCR. Methylation-burden and KRAS-mutation were detected by using the corresponding kits. Receiver operating characteristic curve analysis and the area under the curve (AUC) was calculated to evaluate diagnostic performance using SPSS software.Results197 of CRC samples were enrolled to screen the best predictive combination among fecal immunochemical test (FIT), M3 expression and KRAS-mutation in feces, and Methylation-burden in blood. Single factor analysis showed that M3 expression showed the best diagnosis performance and fecal immunochemical test (FIT) showed the lowest AUC. Combination of two makers universally enhanced diagnostic performance, of which Methylation-burden and M3 alliance displayed the highest AUC value. Interestingly, combination of M3, Methylation-burden and KRAS-mutation reached the best performance for all patients (AUC: 0.920), especially for early CRC patients (AUC: 0.931), which possessed the same predictive efficiency with the combination of four factors.ConclusionCombined application of M3, Methylation-burden and KRAS-mutation might be the most reliable method for early CRC diagnosis.